The Urgency of Making Schools Mini Nutrition Service and Fulfillment Units to Accelerate the Implementation of Free Nutritious Meals in Indonesia - K.P.Suharyono S.Hadiningrat; Mardiana; Fitry Taufiq Sahary; Amrin Soamole; Sukardi (Yayasan Inspirasi Merah Putih Indonesia, 2025)
Efforts to achieve Indonesia's national goals require the state to ensure adequate nutrition for the population through the Free Nutritious Meals (MBG) program launched by President Prabowo Subianto on January 6, 2025, with a target of 28.9 million beneficiaries. The challenge is not easy, given Indonesia's vast territory and ongoing connectivity issues between islands, making it urgent to establish schools as Mini SPPGs. This research design is qualitative with a descriptive explanatory approach to identify and describe research variables narratively and thematically, using standard Indonesian language. The data obtained were categorized into those related to the current SPPG or SPPG Maxi and schools as Mini SPPGs, then narrated according to the research framework and objectives. The qualitative analysis concluded that it is very important and urgent for the Indonesian government to establish schools as Mini SPPGs to accelerate the provision and delivery of nutrition services to the community (students) across all regions of Indonesia, in addition to the existing SPPG (Maxi) system. Supporting factors include the availability of school infrastructure and school committees across all regions of Indonesia. The number of beneficiaries is relatively small, limited to a single school, and collaboration among the pentha helix is needed to strengthen the initiative.